2015
DOI: 10.7314/apjcp.2015.16.13.5169
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study of Adjuvant Chemotherapy Effects on Survival Rate after Three-Field Lymph Node Dissection for Stage IIA Esophageal Cancer

Abstract: To determine the efficacy of postoperative adjuvant chemotherapy with paclitaxel plus cisplatin (Taxol + DDP, TP therapy) for stage IIA esophageal squamous cell carcinoma (ESCC) and to investigate the expression of RUNX3 in lymph node metastasis-negative esophageal cancer and its relationship with medical prognosis, a retrospective summary of clinical treatment of 143 cases of stage IIA esophageal squamous cell carcinoma patients was made. The patients were divided into two groups, a surgery alone control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…To date, the most common treatment for esophageal cancer is surgery, chemotherapy and radiotherapy, in combination. However, the curative effects of 5-fluorouracil (5-FU) and cisplatin (DDP), two basic clinical chemotherapeutic drugs for esophageal cancer, is unsatisfactory in patients with highly metastatic esophageal cancer ( 37 , 38 ). It has been reported that epigenetic behaviors, such as DNA methylation, play important roles in the development and metastasis of esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the most common treatment for esophageal cancer is surgery, chemotherapy and radiotherapy, in combination. However, the curative effects of 5-fluorouracil (5-FU) and cisplatin (DDP), two basic clinical chemotherapeutic drugs for esophageal cancer, is unsatisfactory in patients with highly metastatic esophageal cancer ( 37 , 38 ). It has been reported that epigenetic behaviors, such as DNA methylation, play important roles in the development and metastasis of esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%